2004
DOI: 10.1038/sj.gt.3302298
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the distinct orthotopic bone-forming activity of 14 BMPs using recombinant adenovirus-mediated gene delivery

Abstract: Efficacious bone regeneration could revolutionize the clinical management of bone and musculoskeletal disorders. Although several bone morphogenetic proteins (BMPs) (mostly BMP-2 and BMP-7) have been shown to induce bone formation, it is unclear whether the currently used BMPs represent the most osteogenic ones. Until recently, comprehensive analysis of osteogenic activity of all BMPs has been hampered by the fact that recombinant proteins are either not biologically active or not available for all BMPs. In th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

26
705
3
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 519 publications
(735 citation statements)
references
References 83 publications
26
705
3
1
Order By: Relevance
“…The key step is the generation of recombinants in AdEasier cells. Once these recombinants are obtained, generation of adenoviruses in HEK-293 cells is virtually guaranteed [23][24][25][26][27] . Depending on the transfection efficiency of HEK-293 cells, one can expect titers in the initial lysate to be 10 8 -10 10 pfu ml À1 .…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…The key step is the generation of recombinants in AdEasier cells. Once these recombinants are obtained, generation of adenoviruses in HEK-293 cells is virtually guaranteed [23][24][25][26][27] . Depending on the transfection efficiency of HEK-293 cells, one can expect titers in the initial lysate to be 10 8 -10 10 pfu ml À1 .…”
Section: Anticipated Resultsmentioning
confidence: 99%
“…BMP antagonist, noggin inhibited BMP2 osteogenesis, however SMAD phosphorylation by BMP9 was not inhibited by exogenous noggin (Bergeron et al, 2009; Nakamura, Shinohara, Momozaki, Yoshimoto, & Noguchi, 2013; Wang et al, 2013). BMP3, a known BMP2 inhibitor, did not inhibit BMP9‐mediated bone formation (Kang et al, 2004). Further research utilizing rhBMP9 would benefit our understanding on the differential mechanisms that regulate osteogenesis in both BMP2 versus BMP9.…”
Section: Discussionmentioning
confidence: 99%
“…Although these previous studies were confirmed only utilizing BMP9‐adenovirus‐transfected cells not approved by the FDA (Cheng et al, 2003; Kang et al, 2004; Lamplot et al, 2013; Leblanc et al, 2011), our research group recently characterized the regenerative potential of rhBMP9 in comparison to rhBMP2. In two studies, it was found that rhBMP9 demonstrated up to 10 times greater osteogenic differentiation when compared to rhBMP2 (Fujioka‐Kobayashi et al, 2016a, 2016b).…”
Section: Introductionmentioning
confidence: 85%
See 1 more Smart Citation
“…Moreover, since BMPs are known inducers of osteogenic differentiation, 24 and a local increase of synthesis of several BMPs in the peri‐prosthetic tissue has been reported,23 we also stimulated cells with OM supplemented with either BMP‐2 or BMP‐6. Several BMPs, including BMP‐2 and BMP‐6, have shown positive effects on bone formation, fracture healing, and implant osseointegration in several in vitro and in vivo animal models 30, 31, 32, 33. BMP‐2 is even used in clinical practice for accelerated healing of fractures and for spinal fusions 30, 34.…”
Section: Discussionmentioning
confidence: 99%